Pengaruh Green Marketing dan Corporate Social Responbility terhadap Keputusan Pembelian (Studi kasus : Produk Wardah Beauty) - Siti khodijah; Mas'ut; Dinda thalia sabila; Nita Azhari Simanjuntak (Jurnal Riset Mahasiswa Akuntansi, 2025)
The phenomenon of global warming encourages society and producers to pay more attention to environmental aspects, including in the cosmetics industry. Consumers are now increasingly aware of the importance of choosing environmentally friendly products, thus encouraging companies to use Green Marketing and Corporate Social Responsibility (CSR) strategies. This study aims to determine the effect of Green Marketing and CSR on purchasing decisions for Wardah products in Medan City. This study uses an associative quantitative method with a sample of 50 Wardah product users. Data were collected through questionnaires and analyzed using SPSS V20, including validity tests, reliability, classical assumptions, multiple linear regression, F test, t test, and coefficient of determination. The results of the study indicate that Green Marketing and CSR simultaneously and partially have a positive and significant effect on purchasing decisions.